Morphological traits and high resolution RAPD markers for the identification of the main strawberry varieties cultivated in Argentina - Garcia, Maria Gabriela (2002)
Eight genotypes of the main Fragaria x ananassa cultivars grown in Argentina were analysed using the random amplified polymorphic DNA (RAPD) technique combined with electrophoresis in polyacrylamide gels. The high resolution of this procedure allowed the detection, with only 13 random primers, of 37 genotype-specific bands that can be used as markers for verifying the identity of cultivars. By using this approach, three di erent accessions of the cultivar `Pájaro' exhibited di erences in amplification profiles, confirming the need for DNA analysis to prevent misidentification of cultivars. In addition, RAPD bands and morphological traits were used to assess genetic relatedness among cultivars. Comparison of both dendrograms revealed that there is no correlation between the clustering obtained with molecular and morphological characters.